(3EOGQI GdJShjb GdOhdj hGdYGdej GdeYGUQ hGdMOjK (B:s (3eONd Ydej eJcGed (B/s - (3GdMQjQj, eMeO SQhQs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3eONd ESJQGJjLj Gdi EOGQI GdJShjb GdOhdj hGdYGdej GdeYGUQ hGdMOjK , eONd YGe dGOGQI GdJShjb GdOhdj hGdYGdej , ESJQGJjLjGJ GdJShjb GdOhdj hGdYGdej GdeYGUQ hGdMOjK , GdESJQGJjLjGJ GdMOjKI aj efXeGJ GdJShjb GdOhdjIs
(3eQGLY U(B.181s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdOhdjs; (3GdJShjb(B- (3efXeGJ OhdjIs